ANALISIS PEMBERLAKUAN PAJAK UMKM TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK UMKM - Alfian, Nurul; Saiful, Saiful; Gazali, Gazali; Bustaram, Isnain; Djaja, Herman; Amar, Siti Salama (JURNAL AKUNTANSI DAN INVESTASI, 2021)
The Analysis of tax enforcement through the level of tax compliance UMKM at Surabaya city. The formulation of the problem in this research is how the tax compliance growth of taxpayer at the taxpayer after the transfer of PP number 46 year 2013 to PP number 23 year 2018. The purpose of this study is to find out if any changes to the government regulation affect taxpayers compliance in fulfilling obigations. This research includes descriptive research, the technique to collect theses writing data using questionnaire methods. The data used is primary data. The results showed that UMKM have received government regulation No. 23 year 2018. This is seen from the dominant UMKM respondents answered agree with the taxpayer's understanding indicators, and the tax sanctions on the taxpayer's level of compliance .